An RCT protocol of varying financial incentive amounts for smoking cessation among pregnant women - Lynagh Marita; Bonevski Billie; Sanson-Fisher Rob; Symonds Ian; Scott Anthony; Hall Alix; Oldmeadow Christopher (BMC, 2012)
Abstract Background Smoking during pregnancy is harmful to the unborn child. Few smoking cessation interventions have been successfully incorporated into standard antenatal care. The main aim of this study is to determine the feasibility of a personal financial incentive scheme for encouraging smoking cessation among pregnant women. Design A pilot randomised control trial will be conducted to assess the feasibility and potential effectiveness of two varying financial incentives that increase incrementally in magnitude ($20 vs. $40AUD), compared to no incentive in reducing smoking in pregnant women attending an Australian public hospital antenatal clinic. Method Ninety (90) pregnant women who self-report smoking in the last 7 days and whose smoking status is biochemically verified, will be block randomised into one of three groups: a. No incentive control group (n=30), b. $20 incremental incentive group (n=30), and c. $40 incremental incentive group (n=30). Smoking status will be assessed via a self-report computer based survey in nine study sessions with saliva cotinine analysis used as biochemical validation. Women in the two incentive groups will be eligible to receive a cash reward at each of eight measurement points during pregnancy if 7-day smoking cessation is achieved. Cash rewards will increase incrementally for each period of smoking abstinence. Discussion Identifying strategies that are effective in reducing the number of women smoking during pregnancy and are easily adopted into standard antenatal practice is of utmost importance. A personal financial incentive scheme is a potential antenatal smoking cessation strategy that warrants further investigation. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR) number: ACTRN12612000399897